2022
DOI: 10.1038/s41598-022-26831-6
|View full text |Cite|
|
Sign up to set email alerts
|

The immunolocalization of cluster of differentiation 31, phalloidin and alpha smooth muscle actin on vascular network of normal and ischemic rat brain

Abstract: Cluster of differentiation 31 (CD31), phalloidin and alpha smooth muscle actin (α-SMA) have been widely applied to label the cerebral blood vessels in the past years. Although CD31 is mainly used as endothelial marker in determining the cerebral capillaries, it seems likely that its labeling efficiency is closely correlated with the antibodies from the polyclonal or monoclonal one, as well as the conditions of blood vessels. In order to test this phenomenon, we compared the labeling characteristics of goat pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…CD31 antibodies, widely used as an endothelial marker, are used to immunostain existing and developing brain blood vessels under both physiological and pathological conditions [ 66 ]. The results of our immunohistochemical studies using the endothelial marker CD31 showed a significant increase in the intact vessels number of the microcirculatory bed in the perifocal region of the infarction when the studied peptides were used ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…CD31 antibodies, widely used as an endothelial marker, are used to immunostain existing and developing brain blood vessels under both physiological and pathological conditions [ 66 ]. The results of our immunohistochemical studies using the endothelial marker CD31 showed a significant increase in the intact vessels number of the microcirculatory bed in the perifocal region of the infarction when the studied peptides were used ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cell motility is also closely related to the polarization distribution of cytoskeletal proteins [16,24,25]. Phalloidin has a high affinity for actin and can selectively bind filamentous actin (F-actin) without binding monomeric actin (G-actin) [26,27]. This study used green fluorescent phalloidin to examine the expression and distribution of F-actin in mouse NK cells during cell migration in microfluidic chips.…”
Section: Activin a Promotes Polarization Of Mouse Nk Cellsmentioning
confidence: 99%
“…Compared to the control group, the expression of β-catenin and vimentin was enhanced in activin A-treated NK cells, and the expression of MMP2, which is involved in ECM degradation, was also significantly increased (Figure 4B). actin (F-actin) without binding monomeric actin (G-actin) [26,27]. This study used green fluorescent phalloidin to examine the expression and distribution of F-actin in mouse NK cells during cell migration in microfluidic chips.…”
Section: Activin a Promotes Polarization Of Mouse Nk Cellsmentioning
confidence: 99%